Evaluasi Model CIPP pada Pembelajaran PAI dan Budi Pekerti di SMA Negeri 1 Tikep - Arman Saputra; Nurlathifah Thulfitrah B (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2026)
This article aims to explore the evaluation of the context, inputs, processes, and products of the implementation of Islamic Religious Education and Character Education at SMA Negeri 1 Tikep. Until now, there are still many obstacles faced by a number of educational institutions, especially in the aspects of implementation and evaluation. This study uses a qualitative approach and a type of evaluation research with the CIPP (Context, Input, Process, and Product) evaluation model, which was developed by Stufflebeam. This research was conducted by analyzing the data to answer the problem formulation without testing the hypothesis. The main data from this study were obtained through descriptive analysis, with the data collection process through interviews, documentation, and Post-Test as additional data. The results of this study indicate that from the perspective of the CIPP evaluation model developed by Stufflebeam, the context, input, process, and product aspects of PAI and Budi Pekerti learning based on the 2013 curriculum at SMA Negeri 1 Tikep  are included in the good category.